Status of Seagrass Beds in the Waters around Bahowo, Tongkaina Village, Manado City North Sulawesi Province - Togolo, Festy; Menajang, Febry S. I; Manginsela, Fransine B; Kondoy, Khristin I. F; Lasabuda, Ridwan; Schaduw, Joshian N (Sam Ratulangi University, 2023)
This research was conducted in November 2021 in the waters around Bahowo, Tongkaina Village, Manado City, North Sulawesi Province. Seagrass sampling was carried out using a random sampling method (randomly) with a quadratic transect drawn perpendicular to the shoreline. Thus, 6 species of seagrass were obtained, namely Enhalus acoroides, Halophila ovalis, Thalassodendron ciliatum, Thalassia hemprichii, Syringodium isoetifolium and Halodule pinifolia, with various aquatic environmental conditions. The results of the analysis of the status of the seagrass beds obtained that the seagrass cover value was 50.20% which was included in the